The Berenstain bears ready, get set, go! - Berenstain, Stan, 1923-; Berenstain, Jan, 1923- (New York : Random House, 1988)
The Bear family engage in competitive sports events while demonstrating to the reader the comparison of adjectives.
Keywords: Bears -- Fiction; Sports -- Fiction; Stories in rhyme